Pengaruh Minat Belajar dan Kedisiplinan Siswa Terhadap Hasil Belajar Siswa - Oknaryana Oknaryana; Oktapiana Irfani (Jurnal Ecogen, 2022)
This research aims to determine and analyze the effect of student interest and discipline on learning outcome of economic subjects at SMA Negeri 1 Bintan Utara. This type of research used is ex post facto, the population used is all students of class XI IPS at SMA Negeri 1 Bintan Utara totaling 96 students with a sample of 78 students taken using proportional random sampling Technique. In this study, the instrument used was a questionnaire with Likert Scale model. The instrument validity uses the collected item-total correlation and for reliability testing uses the alpha coefficient formula. The analysis prerequisite test used is the normality test, multicoloniarity, heteroscedasticity test. The data analysis technique used is multiple linear regression analysis technique using SPSS 20. The results of the study showed that: (1) Student’s interest in learning had a significant effect on learning outcomes of economic subjects at SMA Negeri 1 Bintan Utara (2) Student discipline had a significant effect on learning outcomes of economic subjects at SMA Negeri 1 Bintan Utara (3) Interest in learning and student discipline have a significant influence on Economic Learning Outcomes at SMA Negeri 1 Bintan Utara.Keywords : interest to learn, student discipline, student learning outcomes